2012
DOI: 10.4103/0973-029x.99084
|View full text |Cite
|
Sign up to set email alerts
|

Dens invaginatus (Type III B)

Abstract: Dens invaginatus or ‘dens in dente’ is a developmental malformation of the tooth resulting from infolding of the dental papilla before calcification. This article presents a case of dens invaginatus occurring in maxillary right lateral incisor of a 45-year-old male patient. The patient presented with pain and clinically missing maxillary right canine. The tooth was found to be non-vital. Radiographic examination revealed the tooth-in-tooth appearance of lateral incisor with a dilated pulp chamber. The crown of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 12 publications
0
17
0
9
Order By: Relevance
“…Similarly, some authors also reported cases of impacted radicular dens invaginatus. 6,12 Radiographic analysis allowed the observation of an area with high radiopacity compatible with enamel around every dental element, including the radicular portion, a characteristic also observed by other authors, 10 which contributed to ruling out the possibility of this amorphous dental element, the gemination tooth, or the fusion with a supernumerary tooth. To obtain further evidence for the diagnosis, and allow the surgery to be performed accurately and safely, we nominated for CBCT.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Similarly, some authors also reported cases of impacted radicular dens invaginatus. 6,12 Radiographic analysis allowed the observation of an area with high radiopacity compatible with enamel around every dental element, including the radicular portion, a characteristic also observed by other authors, 10 which contributed to ruling out the possibility of this amorphous dental element, the gemination tooth, or the fusion with a supernumerary tooth. To obtain further evidence for the diagnosis, and allow the surgery to be performed accurately and safely, we nominated for CBCT.…”
Section: Discussionmentioning
confidence: 65%
“…4 Teeth with dens invaginatus may have esthetic compromise, occlusal problems, early development of caries and subsequent necrosis of the pulp, 5 or tooth impaction. 6 The treatment of dens invaginatus depends on the degree of invagination and morphological abnormalities, and may include prevention of dental caries and dental restoration to more radical procedures, such as endodontic treatment 5 or extraction of the affected tooth. 1,6,7 The early diagnosis of all forms of dens invaginatus is fundamental for the correct treatment.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…There are other classifications of DI in the literature (Ulmansky and Hermel,7 Vincent-Townend,4 and Schulze and Brand8), but Oehler's classification is widely accepted for its simplicity and ease of practical application 9 10. The types of DI vary in frequency of occurrence with type 3 being the rarest, comprising 5%, compared to type 1 (79%) and type 2 (15%) 9 11…”
Section: Discussionmentioning
confidence: 99%
“…In teeth affected by DI, the invagination of enamel organ and the presence of malformed or absent enamel cause the accumulation of debris, facilitating the fast progression of dental caries and subsequent involvement of the pulp, leading to periapical or periodontal abscess (Kaneko et al, 2011;Kallianpur et al, 2012;Ceyhanli et al;Vier-Pelisser et al, 2014;Capar et al). Thus, the dental problems in DI are mainly related to the degree of bacterial invasion along the enamel invagination (Narayana et al, 2012).…”
Section: Discussionmentioning
confidence: 99%